1993
DOI: 10.2176/nmc.33.552
|View full text |Cite
|
Sign up to set email alerts
|

Acute Subdural Hematoma

Abstract: We devised a linear discriminant function to predict the outcome for patients with acute subdural hematoma (ASDH) based on a consecutive series of 170 ASDH cases with mild to severe head injury [Glasgow Coma Scale (GCS) 3-15]. Functional recovery was achieved in 50.0% of patients and the mortality was 36.5%. The relationship between initial clinical and radiological signs and the outcome 3 months after admission was studied retrospectively by Mann-Whitney's U-test and Pearson's chi-squared test. Fourteen facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It was noticeable that all the recurrences occurred in the fi rst month after discharge from hospital and no recurrences occurred in the following 5 months. Some authors claim that BHC is inadequate to treat so-called septated, multi-loculated or multi-layered hematomas and propose a craniectomy-membranectomy [5] or endoscopic surgery in such cases [21] . In our series there were 8 cases of septated hematomas.…”
Section: Recurrencesmentioning
confidence: 99%
“…It was noticeable that all the recurrences occurred in the fi rst month after discharge from hospital and no recurrences occurred in the following 5 months. Some authors claim that BHC is inadequate to treat so-called septated, multi-loculated or multi-layered hematomas and propose a craniectomy-membranectomy [5] or endoscopic surgery in such cases [21] . In our series there were 8 cases of septated hematomas.…”
Section: Recurrencesmentioning
confidence: 99%
“…It has been established in the literature that SDHs have a high associated morbidity [2-9]. However, larger collections of retrospective data on this patient population are allowing us to determine variables that make patients with SDHs more likely to have a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, mortality among patients with traumatic acute SDHs treated surgically is high, with a range of 30%-70% reported [2-9]. More recent studies have demonstrated a 12%-15% mortality rate for SDHs overall [1, 10-11].…”
Section: Introductionmentioning
confidence: 99%
“…ASDH are present in approximately one third of patients with severe traumatic brain injury. 22) Despite advances in emergency medical services and surgical techniques, ASDH remains one of the most lethal of all intracranial injuries. Various surgical modality such as simple burr hole trephination, CO, and DC are used for evacuation of ASDH.…”
Section: Discussionmentioning
confidence: 99%
“…Acute subdural hematomas (ASDH) are observed in one third of patients with severe traumatic brain injury. 22) ASDH forms between the dura and arachnoid membranes usually due to tearing of bridging veins or arterial rupture. Management of ASDH may vary from simple observation to different surgical evacuation technique.…”
Section: Introductionmentioning
confidence: 99%